COMMUNITY INTENTION IN THE WHISTLE-BLOWING SYSTEM DEVELOPMENT FOR SMOKE-FREE ZONES' LAW ENFORCEMENT IN KENDARI CITY, SULAWESI TENGGARA PROVINCE, INDONESIA - Sagala, La Ode Hasnuddin S.; Saktiansyah, La Ode Ahmad; Ahsan, Abdillah (YCAB Publisher & IAKMI SULTRA, 2020)
Background: Kendari City has set regional regulation No. 16 of 2014 about smoke-free zones (SFZs), however, it has been no tool that is optimal in law enforcement on the application of SFZs regulation in this region.Objectives: This study aims to measure the factors of community intentions in the development of the whistle-blowing systems (WBS) in law enforcement of the SFZs regulation in Kendari City.Methods: The action research approach was carried out with the development of the WBS application which was followed by an observational survey of the community at eight SFZs that had been set in Kendari City.Results: The WBS application for SFZs regulation enforcement in Kendari City was developed through two interfaces: the website on the law enforcement team (Pamong Praja official police and the Health Office) and an Android-based application that can be downloaded for free on the reporting side. Most people of Kendari City have good intentions (90.2 %) in using WBS for SFZs regulation enforcement. This intention indirectly tends to get support from the community (ORadj = 5.1). The age of teenagers or students has the highest proportion in intending to use the WBS for SFZs regulation law enforcement other than employees of private (ORadj = 3.2).Conclusion: Almost the entire community of Kendari intends to use the WBS to SFZs regulation law enforcement also seen indirectly through social supports. This intention related to the age group of adolescents and the type of work of private employees. Further studies are needed to make one of the SFZs as a pilot project in the implementation of the WBS, e.g. educational institutions as a place for teenagers/students.